II LIST OF CHROMOSAN LUIS POTOSIHERIC FLARES FROM OCTOBER 1ST TO DECEMBER 31TH 1957 - RIVERA TERRAZAS, LUIS; GONZALEZ C, GUILLERMINA (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1961)
We present a second list of the observed solar flares during the third trimester of 1957. Therefore lists I and II contain the observed data on solar flares of the first six months of the International Geophysical Year.
BOL OBS TONAN TACUB
Keywords: LIST, CHROMOSPHERIC, FLARES, OCTOBER, DECEMBER, 1957; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS